Increasing of Naphthenes Content in Naphtha by Using Y and  Zeolite Prepared from Iraqi Kaolin - Sarmad Abdul-Razzaq Rashid (Journal of Engineering, 2023)
This work dealt with separation of naphthenic hydrocarbons from non-naphthenic hydrocarbons and in particular concerns an improved process for increasing the naphthenes concentration in naphtha, The separation was examined using adsorption by Y and  B zeolite in a fixed bed process. The concentration of naphthenes in the influent and effluent streams was determined using PONA classification. The effect of different operating variables such as feed flow rate (2- 4 L/hr); bed length (50 - 80 cm) on the adsorption capacity of Y and  zeolite was studied. Increasing the bed length lead to increase the naphthenes concentration, and increasing the flow rate lead to decrease in the concentration of naphthenes, It was found that the decrease in flow rate to 2 L/hr and increase the bed length to 80 cm lead to increase the naphthenes concentration from 6.2 to 24.8 Wt. %.